High‐strength electrically conductive fibers: Functionalization of polyamide, aramid, and polyester fibers with PEDOT polymer. (1st August 2017) - Bashir, Tariq; Skrifvars, Mikael; Persson, Nils‐Krister
Abstract : In this work, high‐performance fibers such as aramid (Twaron), polyamide (PA6), polyester (PET), and hybrid Twaron/PA6 fibers were transformed into electroactive fibers by coating them with conjugated polymer, poly(3, 4‐ethylenedioxythiophene) (PEDOT) through vapor phase polymerization (VPP) method. The VPP is considered as an efficient technique for depositing CPs on different substrates regardless of their lower solubility in various solvents. In this paper, PEDOT‐coated high‐performance fibers were prepared under already optimized reaction conditions, and then a comparison between electrical, thermal, and mechanical properties of different fibers, before and after coating, was made. The obtained coated fibers were characterized through scanning electron microscope (SEM), thermogravimetric analysis (TGA), 2‐probe electrical resistance measurement method, and tensile testing. It was revealed that at particular reaction conditions, all high performance textile substrates were successfully converted into electroactive fibers. The voltage‐current ( V‐I ) characteristics showed that PEDOT‐coated polyester fibers exhibited highest conductivity value among all other substrate fibers. The active PEDOT layers on high performance fibers could behave as an antistatic coating to minimize the risks associated with static charges at work places. Also, the obtained fibers have potential to be used as smart materials for various medical, sports, and military applications.